THE IMPLEMENTATION OF THE SCIENTIFIC APPROACH TO FIQH LEARNING OUTCOMES OF STUDENTS OF MTS SHAFI'IYAH BESUK PROBOLINGGO - Ayu Sha'baniah, Diyah; Azis Wahab, Abd.; Muzammil, Ahmad (Qawwam : The Leader's Writing, 2025)
The purpose of this study is to analyze the application of the scientific approach in fiqh learning and identify the challenges faced by teachers and students at MTs Syafi'iyah Besuk Probolinggo. The main problem found is the low enthusiasm of students and the lack of maximum implementation of fiqh learning which is still teacher-centered. The scientific approach was chosen as a solution to improve fiqh learning outcomes through five steps: observing, questioning, trying, reasoning, and communicating. This research uses descriptive qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The results showed that the application of the scientific approach was able to increase active participation and student understanding of fiqh material. However, there are several obstacles such as limited learning media, lack of training for teachers, and low student discipline. Therefore, although the scientific approach has great potential in improving the quality of fiqh learning, comprehensive support from the school and teachers is needed.